2006
DOI: 10.1109/lpt.2005.861266
|View full text |Cite
|
Sign up to set email alerts
|

Excited state absorption in the Si nanocluster-Er material system

Abstract: Abstract-The issue of Er 3+ excited state absorption in the Si nanocluster-Er material system is highlighted, and an analysis incorporating this interaction presented. We compare our analysis with a prior model of this material, and with regard to previously reported photoluminescence behavior. We show that excited state absorption can explain behavior that has previously been observed, but had not been satisfactorily accounted for.Index Terms-Erbium, optical amplifier, silicon nanocrystal. I. BACKGROUND SILIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…However, when ESA is present, such an increase will not be seen, as excited Er ions can still continue to accept energy from the nanoclusters. 31 We note that our results in this work also show that the nanocluster PL does not increase abruptly when the erbium PL saturates, implying ESA, which will decrease the overall quantum efficiency of the erbium luminescence.…”
Section: ͑15͒supporting
confidence: 52%
“…However, when ESA is present, such an increase will not be seen, as excited Er ions can still continue to accept energy from the nanoclusters. 31 We note that our results in this work also show that the nanocluster PL does not increase abruptly when the erbium PL saturates, implying ESA, which will decrease the overall quantum efficiency of the erbium luminescence.…”
Section: ͑15͒supporting
confidence: 52%
“…6 Various methods have been used to enhance the optical performance of Er 3+ -doped SiO 2 waveguide regardless of the low solubility limit. Some of these methods include utilization of sensitizers such as silicon nanoclusters, [7][8][9][10][11] incorporation of Er in Si x N y , 12 co-implantation of silver in silica glass, 13 preparation of multilayers of Er-doped SiO 2 with silicon rich silicon dioxide ͑SRSO͒, [14][15][16] and synthesis of Er-doped oxide nanostructures. 17,18 Much research effort has also been directed in determining the absorption cross sections for these material systems.…”
Section: Introductionmentioning
confidence: 99%
“…4 In a recent paper, we pointed out the existence of Er excited state absorption ͑ESA͒ occurring in this material system. 8 We propose here that ESA is the primary cause for the low fraction of Er ions excited by the Si-nc.…”
mentioning
confidence: 95%
“…Back-transfer and Auger processes from the Er to the Si-nc were neglected, as it has been experimentally shown that they are unlikely to occur for this material. 11 For simplicity, and in keeping with results from our previous analysis of ESA in this system, 8 the ESA coupling coefficient is taken to be comparable ͑equal͒ to the Si-nc-Er ground state coupling coefficient. We performed the calculations with ESA present, and without ESA for comparison.…”
mentioning
confidence: 99%